Engaging with Terminology in the Multilingual Classroom: Teachers' Practices for Bridging the Gap Between L1 Lectures and English Reading. Issue 1 (2nd January 2017) - Malmström, Hans; Mežek, Špela; Pecorari, Diane; Shaw, Philip; Irvine, Aileen
Abstract: In some academic settings where English is not the first language it is nonetheless common for reading to be assigned in English, and the expectation is often that students will acquire subject terminology incidentally in the first language as well as in English as a result of listening and reading. It is then a prerequisite that students notice and engage with terminology in both languages. To this end, teachers' classroom practices for making students attend to and engage with terms are crucial for furthering students' vocabulary competence in two languages. Using transcribed video recordings of eight undergraduate lectures from two universities in such a setting, this paper provides a comprehensive picture of what teachers 'do' with terminology during a lecture, i.e. how terms are allowed to feature in the classroom discourse. It is established, for example, that teachers nearly always employ some sort of emphatic practice when using a term in a lecture. However, the repertoire of such practices is limited. Further, teachers rarely adapt their repertoires to cater to the special needs arguably required in these settings, or to exploit the affordances of multilingual environments.